(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2025)
The present study evaluated the effect of an aqueous extract of Alai mumiyo on blood coagulation parameters in dogs. Ten healthy adult dogs (12–18 kg) received Alai mumiyo orally at a dose of 50 mg/kg body weight. Blood samples were collected before administration, and at 30 and 60 minutes after treatment, to assess coagulation indices. Administration of Alai mumiyo produced a marked prolongation of blood clotting time, plasma recalcification time, and thrombin time, along with a significant increase in plasma tolerance to heparin. Fibrinogen levels showed a slight, non-significant decrease, while fibrinolytic activity increased moderately. No changes were observed in total plasma protein concentration. These results indicate that Alai mumiyo exerts a clear anticoagulant effect, possibly by modulating both coagulation and fibrinolytic pathways. The findings suggest potential therapeutic value of Alai mumiyo as a natural anticoagulant or antithrombotic agent